Evaluation of the Metabolizable Energy of Poultry By-Product Meal for Chickens and Turkeys by Various Methods - Robbins, D.H.; Firman, J.D. (International Journal of Poultry Science, 2006)
The available energy of several poultry by-product meal products were determined by various experimental methods. It is imperative to determine the accurate available energy value for these products for proper diet formulation and product usage. Leghorn roosters and turkeys were tube fed the products for the assay based on the True Metabolizable Energy (TME) system. Three week old battery reared chicks and poults were fed each product as 50% of a basal diet. The birds were fed for three days with total consumption and excreta measured. Apparent Metabolizable Energy (AME) was then calculated. Endogenous pens were included to make adjustments for AME. Lastly, ileal contents of the chicks and poults were collected to determine ileal AME. There were few differences in assay methodologies noted. Significantly different ME values among assay techniques were found in only four of 15 products. The variable nature of poultry by-product meal led to significant differences in mean ME values among products. There was no difference between pooled AME and TME values, or species. It appears that the TME values commonly determined with Leghorn roosters is acceptable for broilers and turkeys. An effort was made to develop an equation that could predict the TME value of a poultry by-product meal product given the proximate analysis and mineral composition. The first equation, using proximate and mineral data, was inadequate with an R2 = 0.11. Adding the gross energy as a predictor variable greatly improved the effectiveness of the prediction equation (R2 = 0.98).